A Scalable and Secure Protocol for RFID Based on “Advanced Encryption Standard” and Elliptic Curve Cryptography - Couto, Christiana; Dias, Gabriela Moutinho de Souza; Salles, Ronaldo Moreira; Couto, Gustavo Claudio Karl (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2022)
Radio frequency identification systems are widely used to uniquely identify objects in many applications such as magnetic cards, security tags, and logistic management systems. Despite these advantages provided by the RFID system, there remain a multitude of security concerns related to spoofing and espionage that are all concerned with radio frequency interception. Current research analysis is promising, particularly the work of Ibrahim and Dalkiliç. Their findings are, however, limited by the amount of tags that can be processed—which under certain circumstances can exhaust the server. We designed our new protocol and conducted a performance analysis. When compared to the Ibrahim and Dalkiliç's protocol, our results revealed a drastic reduction in the communication cost that was proportional to the amount of tags authenticated. Once the results were tallied, we modeled our proposed protocol in a discrete event simulation. As a proof of concept, our protocol was then implemented in software and analyzed through an experiment whose metrics were: tag identity search speed in the back-end database and amount of tags. Our results show that the proposed protocol offers better performance compared to current standard iterations of similar technology.